Nitrogen addition accelerated straw in-situ decomposition by promoting specific microbial taxa growth and straw decomposing enzyme activities - Guo, Tengfei; Wang, Mengyuan; Chen, Yulu; Yue, Ke; Ma, Long; Huang, Shaomin; Xu, Xinpeng; Song, Xiao; Su, Sumiao; Zhang, Zekun; Zhang, Qian; Zhang, Keke (Frontiers in Plant Science, 2025)
IntroductionCrop residue represents the largest input of organic carbon in agricultural ecosystems and its decomposition is fundamentally mediated by soil microbial communities. However, the mechanism of N fertilization regulating decomposition of the plant residue especially the associated key microbial taxa remain unclear.MethodsTo address this gap, we conducted a 100-day field decomposition experiment using the litterbag method to track temporal shifts in straw physicochemical properties and associated microbial communities under three N regimes: no nitrogen (N0), 200 kg N ha-1 (N200), and 300 kg N ha-1 (N300).Results and discussionsResults showed that nitrogen addition significantly accelerated the decomposition of wheat straw, increasing mass loss and the degradation rates of cellulose, hemicellulose, and lignin relative to N0 treatment. Enzyme activities linked to carbon acquisition, including α-glucosidase (AG), β-glucosidase (BG), cellobiohyrolase (CBH), and β-xylosidase (XYL), were consistently elevated under N-amended treatments during mid- to late-stage decomposition. Similarly, activities of N-acquiring enzymes (β-N-acetyl-glucosaminidase, NAG; leucine aminopeptidase, LAP) and oxidative enzymes (polyphenol oxidase, PPO; laccase) were significantly enhanced, particularly after Day 14. Microbial community succession was tightly coupled with decomposition progression. Random forest modeling identified key bacterial biomarkers (e.g., Terribacillus, Bacillus, Solibacillus, Oceanobacillus, and Cellulosimicrobium) and fungal biomarkers (e.g., Neocosmospora, Actinomucor, Fusarium, Chaetomium, and Aspergillus), all of which are known for their capacity to degrade lignocellulosic and recalcitrant substances. Variation partitioning revealed that straw properties, especially the C/N ratio, TN content, and CBH activity, collectively explained the majority of microbial community variation. These findings support a mechanistic pathway in which nitrogen fertilization reduces residue C/N, thereby reshaping microbial community composition and stimulating enzyme production, which in turn accelerates decomposition. Our study provides novel insights into how nitrogen management influences the coupling of microbial ecology and biogeochemical cycling during straw decomposition, with direct implications for optimizing N fertilization management and sustaining soil fertility in agroecosystems.